Minimal inhibition concentrations of selected antibiotics for strains of Staphylococcus aureus - Sedivá, I; Olejník, P; Rysánek, D (Veterinarni medicina, 1994)
Minimal inhibition concentrations (MIC) of gentamycin (Ge), neomycin (Neo), rifampicin (Rif), ampicillin (Amp), lincomycin (Lin), erythromycin (Ery), and streptomycin (STM) were determined by the agar dilution technique using 46, 130, 131, 125, 140, 139 and 142 strains of Staphylococcus aureus, respectively. The strains, selected from the collection of the authors' laboratory, were isolated from mammary gland secretions of cows affected with clinical or subclinical mastitis. The following ranges of MIC (micrograms/ml) were assessed for the antibiotics under study: Ge 0.125-0.50, Neo 0.06-0.50, Rif 0.0039-0.030, Amp 0.015-1.00, Lin 0.25-1.00, Ery 0.06-0.25, STM 0.50-64.0. Modal MIC (micrograms/ml) were as follows; Ery 0.125 (86%), Lin 0.5 (71.4%), Rif 0.007 (68.7%), Ge 0.25 (56.5%), STM 1.00 (54.2%), Neo 0.25 (53.8%), Amp 0.06 (41.6%). The order of efficiency expressed in MIC 90 (micrograms/ml) was as follows: Rif (0.015), Ery (0.125), Ge (0.25), Neo (0.25), Amp (0.5), STM (4.0).
Keywords: Cattle; Animals; Mammary Glands, Animal; skot; Staphylococcus aureus; mléčné žlázy zvířat; Microbial Sensitivity Tests; zvířata; mikrobiální testy citlivosti; antibakteriální látky; Anti-Bacterial Agents